Distribution of humic substances in sieved aggregates of soil under contrasting land use - Bassey Udom; Achimota Dickson; Gogo Arthur; Miebaka Ikiriko; Babatunde Nuga (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Soil quality indicators that control aggregate stability need o be extensively investigated so as to maintain our soils. Humified carbon (HC), humified acid carbon (HAC), and aggregate-associated fulvic acid carbon (FAC) in forest soils, cocoa plantations, five-year fallow, and five-year continuous cultivated soils were studied. Samples of soil were collected at 0-15 cm topsoil in order to measure the amount of humic materials in both the wet sieved and dry sieved aggregates. Findings revealed a significant input of land use on values of HC, HAC, and FAC occluded in sieved soil aggregates. The HC and FAC were preferentially stored in micro aggregate fractions less than 0.25 mm, while the HAC was greater in macro aggregates 2-1 mm and 1-0.5 mm. Concentration of HC was 18.8 g kg-1 in dry sieved and 17.2 g kg-1 in wet sieved micro aggregates less than 0.25 mm. The HC increased significantly (p<0.05) under a 5-year fallow. The HAC was stored in macro aggregates larger than 1 mm, whereas the HC and FAC fractions were occluded in micro aggregates > 1.0 mm. Continuous cropping decreased MWD of water-stable aggregates by 55%, while bulk density increased by 18%. The correlation coefficient between HC and MWD was significant (r = 0.811, p < 0.01), revealing the positive role of HC in aggregate stability. This study will help in understanding soil management strategies that will raise the accumulation of HC and HAC in macro-aggregates, thereby protecting the soil mass from structural degradation.